Portrait of Career Awareness Elementary School Children: A Preliminary Research - Lidyasari, Aprilia Tina; Hidayah, Nur; Triyono; Hambali, IM. (International Journal of Psychosocial Rehabilitation, 2020)
-The purpose of this research is to describe the child’s career awareness in elementary school that comprises aspects of self knowledge, education and career relationships, career planning, career assignments and benefits. The study used quantitative descriptive analysis using the Child Career Awareness Scale (CCAS), an open questionnaire and interviews. Respondents numbered 93 children in grade 4 in elementary schools in Kulonprogo Yogyakarta. CCAS results show 53 (56%) of that low-category. The low career awareness is shown per an aspect of self knowledge 33 (36%), educational and career relationships 34 (37%), career planning 44 (47%), 34 (37%) assignment career variety, benefits of career varietys 37 (40%). The results of the open questionnaire 47 (51%) of respondent can correctly refer to their career variations and assignment. While the results of interviews on children are deduced the majority of children mention work and ideas but do not know its ability, shortcomings, education plans, career planning, assignment from career varietyand benefits. The results of interviews with elementary school teachers have not yet had a special guide on the career awareness of elementary school children. It can be concluded that the career awareness of elementary school children needs to be increased optimally at the beginning of its development so it is advised that the results of the study of the children’s career awareness in elementary school.